A Search for Coincident Neutrino Emission from Fast Radio Bursts with Seven Years of IceCube Cascade Events - R. Abbasi; M. Ackermann; J. Adams; S. K. Agarwalla; J. A. Aguilar; M. Ahlers; J. M. Alameddine; N. M. Amin; K. Andeen; G. Anton; C. Argüelles; Y. Ashida; et al. (The Astrophysical Journal, 2023)
This paper presents the results of a search for neutrinos that are spatially and temporally coincident with 22 unique, nonrepeating fast radio bursts (FRBs) and one repeating FRB (FRB 121102). FRBs are a rapidly growing class of Galactic and extragalactic astrophysical objects that are considered a potential source of high-energy neutrinos. The IceCube Neutrino Observatory’s previous FRB analyses have solely used track events. This search utilizes seven years of IceCube cascade events which are statistically independent of track events. This event selection allows probing of a longer range of extended timescales due to the low background rate. No statistically significant clustering of neutrinos was observed. Upper limits are set on the time-integrated neutrino flux emitted by FRBs for a range of extended time windows.